Analisis Faktor –faktor Yang Menjadi Pertimbangan Wisatawan Untuk Mengunjungi Obyek Wisata Penelokan Kintamani Bangli Bali - I Made Hedy Wartana (Jurnal Ilmiah Hospitality Management, 2010)
The development of tourism in Indonesia in general and Bali in particular that continues to move dynamically, and the tendency of tourists to travel is an opportunity and challenge to tourism in Bali, so there should be reform, especially services for tourists to feel comfortable to visit. Bangli District has many attractions such as Penelokan Kintamani Bangli, tour Penglipuran. Attractions have been able to increase the number of tourist visits to District Bangli. The formulation of the problem is 1.Faktor-factor into consideration whether the tourists visiting the tourist attraction Kintamanai Penelokan Bangli Bali? 2. Where is the dominant factor to be considered tourists visit tourist attractions Penelokan Kintamani Bangli Bali?. This study used 15 variables, so the number of samples taken is as much 15x5 which is 75 responden.Teknik analaisis used were factor analysis and the result is excellence factor has an eigenvalue of 1.347 and the value that determines the percentage of variance in visiting tourists Object Penelokan Kintamani Tour Bali Bangli of 10.361%. Product factors have an eigenvalue of 1.347 and the value that determines the percentage of variance in visiting tourists Object Penelokan Kintamani Bangli Bali Tour of 10.361%. Factors have an eigenvalue value of 1.154 with a value of 8.874% the percentage of variance that determines the tourists in visiting the objects Penelokan Kintamani Bangli Bali Tour of 8.874%.